Understanding resistance mechanisms to BTK and BCL2 inhibitors in mantle cell lymphoma: implications for design of clinical trials. Issue 12 (2nd December 2018) - Agarwal, Rishu; Dawson, Mark A.; Dreyling, Martin; Tam, Constantine S.
Abstract: Novel targeted therapeutics has significantly improved the outlook of patients with relapsed/refractory mantle cell lymphoma (R/R MCL). Despite significant efficacy, one of the major limitations of these targeted agents is presence of primary or acquired resistance to these novel drugs. Patients who fail primary therapy especially with ibrutinib have poor outcomes and may respond poorly to subsequent therapies. Hence, it is important to understand resistance mechanisms a priori to identify patients who are unlikely to respond, and to explore alternative therapeutic strategies. In this review, we will discuss the currently most active two drugs: ibrutinib and venetoclax, both of which have shown high response rates in R/R MCL. We review current understanding of genomic alterations associated with resistance, and discuss possible strategies to overcome these resistance mechanisms.